Habitat Use by Breeding Northern Bobwhites in Managed Old-Field Habitats in Mississippi - Jimmy D. Taylor II; Loren W. Burger Jr. (National Quail Symposium Proceedings, 2017)
To better understand the proximate and ultimate cues associated with habitat selection in breeding northern bobwhites (Colinus virginianus), we compared habitat use vs. availability at 2 spatial scales equivalent to Johnson's (1980) 2nd and 3,d order selection. We conducted the study in managed old-field habitats in Mississippi, from 1994 to 1996. We also estimated habitat use by broods with respect to availability, and quantified micro-habitat characteristics (4th order selection) at brood-rearing sites and nesting sites. Breeding bobwhites did not establish home ranges at random or allocate resources among patches in proportion to their availability. Breeding bobwhites, given a mosaic of seasonally manipulated old-field habitats, consistently used burned fields, disked fields, and areas with advanced woody succession to define breeding season home ranges. Bobwhites allocated their time and resources more to woody areas and fields that had received a combination of burning and disking. Broods consistently used burned/disked fields in proportion to availability; consistently avoided row crops and pastures; and generally preferred woody corridors. Vegetation characteristics at nest sites did not differ from random sites located within the same patch of habitat. Characteristics among nest sites were similar, yet successful nests were located in the proximity of more bare ground and less litter cover than unsuccessful nest sites. Brood site habitat characteristics were similar to nest sites; however, woody canopy (44.3%) and visual obstruction readings (59.0cm) at brood sites were significantly greater than nest sites (26.6% and 32.5cm).